Kelayakan Investasi Rekonstruksi Kapal Tangkap Tuna di PT Perikanan Nusantara (Persero) Cabang Benoa Provinsi Bali - EVITA YULISETIANI; KETUT BUDI SUSRUSA (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2020)
Investment Feasibility for Reconstruction of Fishing Vessels at PT Perikanan Nusantara Ltd, Benoa Branch, Bali Province In this researchwas conducted to determines the feasibility of investing in reconstruction of a fishing vessel owned by PT Perikanan Nusantara Ltd, Branch of Benoa based on financial and non-financial aspects. Analyzing the financial aspects was assessed to be able to calculate revenue, costs, profits and financial parameters NPV, IRR, Net B / C, Payback Period, and sensitivity analysis. Other objectives, namely the assessment of non-financial aspects that are processed to be able to find out the investment feasibility of the market aspects, management aspects, technical aspects, environmental aspects, legal aspects and socio-economic aspects. The results of this research are NPV value isRp 4.791.713.354, IRR>13% is 90,8%, Net BC is 7 with a payback period of 1,14 year. Sensitivity analysis was carried out to determine changes in NPV values ??against increases in cash outflows and decreases in cash inflows. In addition to the assessment of non-financial aspects, non-financial aspects of the market, management aspects, technical aspects, environmental aspects, legal aspects and socio-economic aspects. From all aspects examined in this survey, a decision was made that this investment was declared feasible to run and suggested to continue investment activities.